(untitled) (Conferencea, 2025)
This article covers the history of badminton from ancient times to the modern era. The origins of the game, legends associated with the game of ancient peoples, its popularity in Europe and Asia, as well as the formation of modern rules and international competitions are discussed. The development of badminton in the Soviet era and its current state worldwide are also discussed. This article covers the main events and periods of historical importance in the formation of badminton as a sport.